PEMBUATAN DAN PEMANFAATAN KALIUM FERRAT DALAM PENGOLAHAN LIMBAH ZAT PEWARNA PROCIAN RED MX 8B - Yani Ekwandi Wibowo, ; Nita Kusumawati, (Matematika dan Sains, 2009)
The purpose of this research is to investigate the degradation of procion red MX 8B contain pH effect and molar ratio to degradation it using pottasium ferrate. Synthesis and characterization of pottasium ferrate were performed before it was reacted with procian red MX 8B. The aqueous stability of pottasium ferrate at various pH values and some parameters which influenced the degradation process such as pH and molar ratio of dye:Fe(VI) have been studied. The progress of reaction was followed by UV-Vis spectrophotometry. The aqueous reaction of ferrate with procian red MX 8B was also investigated with a molar ratio of dye:Fe(VI) in the range of 1:1 1:5. The results showed that pottasium ferrate solution had a maximum stability at pH 9-10. The optimal pH for degradation of procian red MX 8B was 9.2 and molar ratio dye:Fe(VI) was 1:1. At this pH and molar ratio dye:Fe(VI) approximately 96.5% were degraded after 30 minutes. Degradation process of procian red MX 8B using pottasium ferrate was marked by the shifting of the wave lenght which it has shifted from 545 nm to 296.2 nm.